2020
DOI: 10.4314/as.v19i3.5
|View full text |Cite
|
Sign up to set email alerts
|

Production and management of goat rearing in rural areas of Ezinihitte Mbaise, Imo State, Nigeria

Abstract: This study assessed production and management practices of indigenous goat rearing in the rural communities of Ezinihitte Mbaise, Imo State. Data were collected from 150 goat farmers in Ezinihitte Mbaise with the use of structured questionnaire in 2014 for data collection. The  questionnaire was on the socio-economic characteristics of goat farmers, factors influencing and constraints on production and management of goat rearing. The mean age of goat farmers was 51 years and 86 percent were males. The farmers’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…This inverse relationship implies that the age of the farmers' increase, their extent of use of improved goat production technologies in the study area decrease. The result is in agreement with Nwachukwu and Berekwu., (2020) that age of respondents is negatively related to adoption of improved production technology.…”
Section: Extent Of Use Of Improved Goat Production Technologiessupporting
confidence: 90%
See 2 more Smart Citations
“…This inverse relationship implies that the age of the farmers' increase, their extent of use of improved goat production technologies in the study area decrease. The result is in agreement with Nwachukwu and Berekwu., (2020) that age of respondents is negatively related to adoption of improved production technology.…”
Section: Extent Of Use Of Improved Goat Production Technologiessupporting
confidence: 90%
“…The result revealed that lack of access to credit (100%), lack of credibility from source (100%), afraid of taking risk (99.2%), difficulty in applying technology (93.3%), farm size is small (86.7%), the technologies expensive to adopt (76.7%), cultural or religious belief (75.8%), lack of vetinary expert (60.8%), procedure were difficult to understand (58.8%) and lack of technical support (57.5%) were the constraints faced by the respondents in their use of improved goat production technologies This result implied that goat farmers encountered series of constraints in the use of goat production technologies. The finding is in tandem with Nwachukwu and Berekwu (2020) that goat farmers were constrained by poor veterinary services, inadequate skilled labour, poor housing facilities, poor road network, market problems, high diseases and pest incidence, high cost of drugs and feeds as major constraints faced by the goat farmers in the study area. More so, Krishna, Mahesh, Lal, and Chhetrib., (2019) found that cost technologies and lack of access to farm credit were hindered goat farmers from adopting improved production technologies.…”
Section: Constraints To Use Of Improved Goat Production Technologiesmentioning
confidence: 63%
See 1 more Smart Citation
“…The field of goat production involves three primary systems: extensive, semi-intensive and intensive (Nwachukwu and Berekwu, 2020). However, there may be variations within each system that depend on the geographic region (Tovar-Luna, 2009).…”
Section: Reproductive Efficiencies and Productive Potentials Of Femalementioning
confidence: 99%
“…The rearing of goats and sheep contribute about 17 % of the total meat and 12 % of milk production in Africa (Lebbie, 2004) and this play a significant role in the improvement of human nutrition (Adam et al, 2010). Goat milk rarely consumed in this part of the world however, there is a growing awareness of the nutritive importance of goat milk to humans (Nwachukwu and Berekwu, 2020). Significant variation has been observed in ruminant feed utilization where goat was reported to have higher feed conversion efficiency to meat and milk than cattle, sheep, and buffaloes (Lebbie, 2004;Nwachukwu and Berekwu, 2020).…”
Section: Introductionmentioning
confidence: 99%